Müslümanlar Neden Teröre Alet Oluyorlar? - Ramazan Biçer (Kader, 2018)
The Thesis states Global Terrorism, is a global project that has no direct place or time is an interesting approach. Although the reason of terrorism has been come down to difference between civilizations and religions; that is not the case. Another reason which is argued is that Muslims are unable to integrate into Western societies. However this is not unique to Muslims, it is also a problem for non-Muslim immigrants.